Land use, flooding regime, and seasons differentially shape composition of beetle species in a semi-arid highland floodplain in Central Kenya - Jane M. Macharia; Mathias Becker; Helida Oyieke; Kai Behn (International Journal of Tropical Insect Science, 2026)
Biodiversity is threatened globally by human-mediated alteration of natural environment. This includes East African wetland ecosystems that are subject to agriculture expansion and intensification. Monitoring of biodiversity is crucial to understand and mitigate biodiversity losses. Beetles, while rarely studied, are potentially useful bioindicators due to their sensitivity to environmental changes. Our study aimed at investigating the influence of land use regimes (cropland, fallow, grazing land, pristine), as well as flooding regimes and seasonality on the abundance, composition, diversity, and occurrence of beetle species in the Ewaso Narok swamp, Kenya. Using pitfall traps and sweep nets over two years (2015–2016) in 42 plots each of six sampling dates, we recorded 2,145 beetles (20 families, 179 species). Conversely to our hypothesis, we only found weak effects of land use on abundance, diversity and species composition. Seasons, and individual sampling dates were more important, partly due to varying rainfall prior to the sampling. Heavy rainfall decreased abundance of ground-dwelling beetles, particularly in the wettest zone. Regarding individual species, most occurred across all land uses and did not show much specificity. However, among ground-dwelling beetles, some species demonstrated significant associations with land use intensity. For instance, disturbance tolerant Tenebrionids such as Zophosis abyssinica and Gonocephalum simplex were associated with high land use intensity (cropland/fallows), while predatory Staphylinid Philonthus circumcinctus was associated with grazing lands. Hence, selected species may act as bioindicators and may represent “winners” and “losers” of land transformations. These results support biodiversity monitoring and future wetland use planning.

Generation of Fibrin-Based Aortic Vessels with Layer-Specific Cell Architecture Under Pulsatile Perfusion in a Clinical Organ Care System - Celina Delia Käding; Clara-Sophie Glomb; Patrick Stadler; Imke Becker; Melanie Klingenberg; Hans-Klaus Höffler; Michael Pflaum; Arjang Ruhparwar; Mathias Wilhelmi; Florian Helms (Annals of Biomedical Engineering, 2026)
Purpose Overcoming the limitations of synthetic vascular grafts in the development of biocompatible and regenerative vessels remains a long-term objective in tissue engineering. In this study, we engineered large-diameter fibrin-based vascular grafts with a target inner diameter of 21 mm replicating all three layers of the native human vessel wall in vitro. Methods The Tunica media was reconstructed using a compressed high-density (25 mg/mL) fibrin matrix seeded with smooth muscle cells expressing α-SMA and calponin, differentiated from adipose-derived mesenchymal stem cells (ASCs). The Adventitia -equivalent was formed in a 5 mg/mL fibrin gel containing ASCs, human umbilical vein endothelial cells (HUVECs), and normal human dermal fibroblasts (NHDFs) to enable the formation of a capillary-like network resembling the native adventitial Vasa vasorum . The luminal surface was endothelialized with HUVECs to replicate the Tunica intima . While controls were cultured statically for 7 days, other grafts were evaluated under pulsatile perfusion at physiological pressures using the TransMedics ® “Organ Care System Heart ™ ”. Results The stepwise fabrication technique resulted in three-layered bioartificial vessel equivalents with a mean inner diameter of 21 mm. All constructed vessels ( n = 3) maintained sufficient biomechanical stability to withstand physiological pressure (120.9 ± 1.2 to 61.4 ± 12.5 mmHg) at 60 bpm throughout the perfusion period. The aortic grafts exhibited a cyclic stretch (8.95 ± 2.03%) within the physiological range of native vessels. Mechanical stimulation induced a layer-specific physiological cell morphology and alignment across all three layers of the vascular wall. Endothelial coverage was high on static grafts (81.39 ± 2.37%) and on one of three dynamic grafts. Shear stress during perfusion (0.38 ± 0.03 dyn cm −2 ) remained below physiological levels, and further evaluation under prolonged perfusion (> 21 days) is required to assess long-term biomechanical stability and vascular functionality. Conclusion This approach may be considered a proof of concept and constitutes a first step toward the development of biometric and functional large-diameter vessel replacements.

Recovery dynamics of wetland vegetation along a hydrological gradient in an agriculturally used inland valley in Uganda - Kai Behn; Miguel Alvarez; Samuel Mutebi; Mathias Becker (Wetlands Ecology and Management, 2024)
Wetlands in East Africa are important for providing ecosystem services and for conserving biodiversity. They are also suitable and increasingly used for agriculture. Between cropping cycles, spontaneous vegetation regrows on fallow plots. We hypothesize that recovery is affected by hydro-edaphic conditions and the duration of the fallow period. Land use intensification reduces fallow durations. A multi-year field study investigated the dynamics, biodiversity, and potential uses of fallow vegetation species after a disturbance event in an inland valley wetland in Central Uganda. The wetland was stratified into three hydrological positions along a gradient comprising the valley fringe, the mid-valley, and the riparian zone. In each zone, biomass was removed, and the soil was tilled, simulating a common disturbance event. Subsequently, four plots of 4 × 4 m size were delineated in each zone. Vegetation regrowth was subsequently monitored over a period of two years. We recorded and analyzed changes in aboveground live biomass, abundance of selected plant species, taxonomic and functional composition, and evenness during a 27-months recovery phase. While annual species dominated the vegetation initially, these were gradually replaced by herbaceous perennials, and eventually by tall reeds and woody plants, constituting three successional stages. The dynamics were similar, but species composition differed across the positions. At all successional stages, we observed the presence of useful wild plants, but also invasive species such as Mimosa pigra were recorded. While temporary fallows are important for biodiversity in tropical wetlands, such successions cannot substitute for the functions and services provided by natural vegetation and may promote invasive species.

Potential Improvements in Crop Production in Egypt and Implications for Future Water and Land Demand - Saher Ayyad; Poolad Karimi; Lars Ribbe; Mathias Becker (International Journal of Plant Production, 2024)
Similar to numerous water- and data-scarce regions, Egypt confronts a critical challenge in sustaining food production for its rapidly growing population. Consequently, the country’s water and land resources are under considerable stress and require careful management. About half of Egypt’s both annually harvested areas and renewable freshwater are allocated for cultivating rice, maize, wheat, and berseem clover. However, the extent to which crop production might be improved and how this would impact future water and land requirements remains poorly understood. We analyzed potential improvements in the production of these crops and quantified their future water and land requirements under different scenarios. Potential improvements were detected through percentile analysis in three remote sensing-derived performance indicators for each crop in the Nile Delta’s Zankalon region: (i) crop yield, (ii) crop water productivity, and (iii) transpiration fraction (transpiration to actual evapotranspiration, T/AET). We applied detected improvementsto construct plausible scenarios for Egypt’s water and land requirements to sustain domestic crop production until 2050. Our findings indicate limited potential to improve T/AET (< 4%). However, improvements of up to 27% for crop yields and up to 14% for water productivity are possible. To meet the production targets by 2050, national production must increase by 128, 78, 69, and 71% above the 2016–2020’s average for rice, maize, wheat, and berseem, respectively. Depending on the improvement levels in the developed scenarios, a total harvested land area between 5.3 and 6.4 million ha will be required by 2050, with 18% allocated to rice, 28% to maize, 36% to wheat, and 18% to berseem. Associated freshwater requirements will amount to 59–68 billion cubic meters, divided into 23% for rice, 34% for maize, 28% for wheat, and 15% for berseem. Interventions increasing yields and water productivity will benefit more the summer (rice and maize) than the winter crops (wheat and berseem). We discuss likely interventions for meeting these requirements and for sustaining the supply of these crops in Egypt.

Improving rice yield and water productivity in dry climatic zones of West Africa: Season-specific strategies - Jean-Martial Johnson; Mathias Becker; Elliott Ronald Dossou-Yovo; Kazuki Saito (Field Crops Research, 2024)

Alternate wetting and drying: a water-saving technology for sustainable rice production in Burkina Faso? - Jean-Martial Johnson; Mathias Becker; Jean Eric P. Kaboré; Elliott Ronald Dossou-Yovo; Kazuki Saito (Nutrient Cycling in Agroecosystems, 2024)
With emerging water scarcity and rising fertilizer prices, optimising future water use while maintaining yield and nutrient efficiency in irrigated rice is crucial. Alternate wetting and moderate soil drying irrigation (i.e., re-irrigation when the water level reaches 15 cm below the soil surface) has proven to be an efficient water-saving technology in semi-arid zones of West Africa, reducing water inputs without yield penalty. Alternate wetting and severe soil drying (AWD30), by re-irrigating fields only when the water table reaches 30 cm below the soil surface, may further reduce water inputs compared to farmers’ irrigation practices (FP). However, acute soil drying may impair fertilizer use efficiency and reduce the bio-availability of some key nutrients. This study assessed the potentials and risks associated with AWD30 for smallholder rice farmers in the semi-arid zones of West Africa. We conducted 30 on-farm field trials over three seasons (wet and dry seasons of 2019, and dry season of 2020), in Kou Valley, Burkina Faso. We assessed yield, water productivity, nutrient uptake, and use efficiency under AWD30 and FP. In FP, farmers maintained their fields submerged as frequently as possible according to the scheme-dependent water provision schedule. With AWD30, irrigation frequency was reduced by 30%, however, soils were seldom completely dried due to a shallow groundwater table. Compared to FP, AWD30 reduced irrigation water input by 37% with no significant effects on grain yields (average of 4.5 Mg ha −1 ), thus increasing average water productivity by 39%. Both irrigation management practices provided comparable crop uptake of N, P, and K, and use efficiencies of applied N and P. However, the N content in straw and the P concentration in grain generally increased with total water input (rain + irrigation). We conclude that at locations with a shallow groundwater table, AWD30 can effectively save irrigation water without significantly reducing the grain yield and the use efficiency of applied mineral nutrients.

System shift in rice: Processes and pathways of change in rice-based production systems of Southeast Asia - Mathias Becker; Richelyn Clavero; Ohnmar Min Khin; Sichantha Kong; Zar Ni Maung; Punlork Men; Shyam Pariyar; Manuel José C. Regalado; Sophoanrith Ro; Kyaw Kyaw Win (Agricultural Systems, 2024)

Subsequent primary neoplasms after childhood cancer therapy – design and description of the German nested case–control study STATT-SCAR - Peter Scholz-Kreisel; Cornelia Becker; Melanie Kaiser; Seyed Hamidreza Mahmoudpour; Mathias Voigt; Meike Ressing; Maria Blettner; Gabriele Calaminus; Katja Baust; Cathy Scholtes; Martin Zimmermann; Sylke Ruth Zeissig; et al. (Cancer Causes & Control, 2024)
Background Subsequent primary neoplasms (SPN) are among the most severe late effects and the second most frequent cause of death in childhood cancer patients. In this paper we introduce method and properties of the STATT-SCAR study (Second Tumor After Tumor Therapy, Second Cancer After Radiotherapy), which is a joint nested matched case–control study to evaluate the impact of chemotherapy (STATT) as well as radiotherapy (SCAR) on the risk of developing a SPN. Methods Based on the cohort of the German childhood cancer registry (GCCR), we selected patients diagnosed with a first neoplasm before age 15 or younger between 1980 and 2014. We selected those with a SPN at least half a year after the first neoplasm, and matched up to four controls to each case. Therapy data were acquired from various sources, including clinical study centers and treating hospitals. To analyze the impact of radiotherapy, organ doses were estimated by using reconstructed treatment plans. The effect of chemotherapy was analyzed using substance groups summarized after isotoxic dose conversion. Results 1244 cases with a SPN were identified and matched with 4976 controls. Treatment data were acquired for 83% of all match groups (one case and at least one control). Based on preliminary analyses, 98% of all patients received chemotherapy and 54% of all patients were treated with radiotherapy. Conclusions Based on our data, detailed analyses of dose response relationships and treatment element combinations are possible, leading to a deeper insight into SPN risks after cancer treatments. Trial registration The study is registered at the German clinical trial register (DRKS) under number DRKS00017847 [45].

Reconciling East-African Wetland Conservation with Human Needs: Managing Uncertainties in Environmental Policy Design - Matthias Langensiepen; Erick Omwandho Opiyo; Alice A. Kaudia; Denis Rugege; Kyambadde Richard; Erick Akotsi; Dan Ashitiva; Julius K. Ningu; Faustin Munyazikwiye; Theogene Ngaboyamahina; Justin K. Urassa; Michael Ugen; et al. (Wetlands, 2023)
Rapidly developing societies in East-Africa impose increasing pressures on wetlands due to rising food demand and degradation of upland soils. Reconciling wetland conservation with human needs for food and energy is therefore becoming an increasing contentious issue. Stakeholders and actor coalitions generate and apply a great variety of meanings, values, and interests when interacting with wetlands which are hardly predictable. Wetland policy-making is hence fraught with uncertainties which need to be managed for finding solutions to this problem. Based on experiences of a collaborative wetland research in East-Africa we developed a new wetland policy process framework which promotes social deliberation and reconciliation of plural wetland values to reduce these uncertainties. A new cognitive-driven information design (CDID) method has been developed to assist wetland policy-analysts in achieving these aims and also to overcome limitations of prescriptive decision-making. The method employs information and communication technologies to analyze, integrate and visualize complex socio-ecological wetland information for developing policy scenarios. It is applied at all stages of the wetland policy process including agenda setting, identification of plural wetland values, establishment of decision-scenarios, social deliberation during policy formulation, governmental decision-taking, policy implementation and evaluation. A three-stage implementation process is recommended.

Paleovolcanology, geochemistry, and zircon U-Pb-Hf isotopes of the volcano-sedimentary sequences from the Ediacaran Campo Alegre-Corupá Basin, southern Brazil: Linking volcanism and tectonics during Western Gondwana consolidation - Francy Roxana Quiroz-Valle; Lucas Martins Lino; Sérgio Brandolise Citroni; Miguel Ângelo Stipp Basei; Mathias Hueck; Silvio Roberto Farias Vlach; Bruno Becker-Kerber; Gustavo Marcondes Evangelista Martins Prado (Gondwana Research, 2023)

Action on Invasive Species: Control Strategies of Parthenium hysterophorus L. on Smallholder Farms in Kenya - Martin Paul Tabe Ojong; Miguel Alvarez; Hanna J. Ihli; Mathias Becker; Thomas Heckelei (Environmental Management, 2022)
Parthenium hysterophorus L. (Asteraceae) is an invasive alien weed with detrimental effects on agricultural production, biodiversity, human and animal health, threating rural livelihoods in Asia and Africa. The problem emerged recently in the Kenyan Rift Valley, where it began to affect the landholdings of both agro-pastoralists and crop farmers. These vulnerable smallholders depend heavily on natural resources for their livelihoods. In this study, we assessed the severity of parthenium invasion and farmers’ management responses using a sample of 530 agro-pastoralists in Baringo County, Kenya, in 2019. We hypothesise that the implementation of existing management strategies depends on the state of parthenium invasion and household socio-economic characteristics. The prevalence and severity of parthenium invasion differed greatly among field plots. To control weeds, farmers resort to either hand weeding, the use of synthetic herbicides, or intensive tillage, sometimes in combination with mulching. A multivariate probit regression model shows that households’ characteristics determine the type of control strategies used as well as their complementarity and substitutability. Hand weeding is the most common option, adopted by almost 40% of farmers. The use of agrochemicals or soil-based control strategies appears to be related to knowledge and information characteristics such as access to extension services, membership in organisations and the educational level of household heads. While hand weeding and the use of synthetic herbicides depict significant substitutability, the latter strategy is limited to a few larger farms with market-oriented production. As parthenium invasion continues, policies need to improve farmer awareness and access to knowledge to enable pro-poor and environmentally sustainable control of parthenium on smallholder farms.

Use of selective serotonin reuptake inhibitors, other antidepressant medication, and risk of cataract: a case-control study based on Swiss claims data - Claudia Becker; Matthias Schwenkglenks; Mathias Frueh; Oliver Reich; Christoph R. Meier (European Journal of Clinical Pharmacology, 2020)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Factors influencing farmers’ decisions on nitrogen fertilizer application in the Liangzihu Lake basin, Central China - Jin Zhang; Günther Manske; Pi Qi Zhou; Bernhard Tischbein; Mathias Becker; Zhao Hua Li (Environment, Development and Sustainability, 2017)

Responses of rice to chronic and acute iron toxicity: genotypic differences and biofortification aspects - Michael Frei; Richmond Narh Tetteh; Ando Lalaina Razafindrazaka; Michael Apolonius Fuh; Lin-Bo Wu; Mathias Becker (Plant and Soil, 2016)

Loci, genes, and mechanisms associated with tolerance to ferrous iron toxicity in rice (Oryza sativa L.) - Elsa Matthus; Lin-Bo Wu; Yoshiaki Ueda; Stefanie Höller; Mathias Becker; Michael Frei (Theoretical and Applied Genetics, 2015)

The differential effects of acute right- vs. left-sided vestibular failure on brain metabolism - Sandra Becker-Bense; Marianne Dieterich; Hans-Georg Buchholz; Peter Bartenstein; Mathias Schreckenberger; Thomas Brandt (Brain Structure and Function, 2014)

Dynamics of agricultural use differentially affect soil properties and crop response in East African wetlands - Hellen Kamiri; Christine Kreye; Mathias Becker (Wetlands Ecology and Management, 2013)

Classification, Characterisation, and Use of Small Wetlands in East Africa - Nomé Sakané; Miguel Alvarez; Mathias Becker; Beate Böhme; Collins Handa; Hellen W. Kamiri; Matthias Langensiepen; Gunter Menz; Salome Misana; Neema G. Mogha; Bodo Maria Möseler; Emiliana J. Mwita; et al. (Wetlands, 2011)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)